THE NEED ANALYSIS ON BIKE SHARING SYSTEM AMONG STUDENTS IN UNIVERSITI UTARA MALAYSIA (UUM) (Journal of Technology and Operations Management, 2018)
At the present time bicycle services are becoming important in the public transport due to its good impact on environmental and health issue. Bike Sharing System is a program in which many bicycle stations are set up and peoples can rent a bike to use for a certain time frame and return it at a different station. However, in order to promote cycling culture, a well urban planning along with reliable cycling infrastructure is a must. This article provides the result of a need analysis study on the critical factors in the operation of bike sharing system. The aim of this study is to determine the students’ intention on bike sharing system among STML students based on the impact of bike sharing services. A survey was conducted on undergraduate students to determine the level of the critical factors among the participants based on the year of study. The research instrument for this study is a set of questionnaire that consists of 5-point Likert scale adapted from the Technology Acceptance Model. The outcomes of the study possibly reflect the young generation views on the bike sharing system implementation.